Decision Making for The Most Outstanding Students Award using TOPSIS: a Case Study at Institut Teknologi Sumatera - Pratama, Borneo Satria; Drantantiyas, Nike Dwi Grevika; Marvie, Ilham; Sembiring, Noveliska Br; Nadi, Muhammad Abi Berkah (Journal of Innovation Information Technology and Application (JINITA), 2023)
The internal selection of Pemilihan Mahasiswa Berprestasi, or known as Pilmapres, is an annual competition held by Institut Teknologi Sumatera (ITERA) to award the most outstanding student of the year which will be further sent to compete in regional and national event of Pilmapres held by Balai Pengembangan Talenta Indonesia. This study aimed to implement TOPSIS as a decision-making tool to determine the winner of Pilmapres ITERA in 2023. The criteria used in this study were general achievements, English competencies, and creative ideas, with weight of 50, 20, and 30, respectively. The scores for the criteria for each of the students are obtained from nine members of the board of jury in the final stage of Pilmapres ITERA in 2023. The calculation result using TOPSIS concluded that the 1st, 2nd, and 3rd winners of the internal selection of Pilmapres ITERA in 2023 were Alpha, Beta, and Omega, with the final preference scores of 0.995, 0.799, and 0.795, respectively.